Design and Synthesis of Sulfonium and Selenonium Derivatives Bearing 3′,5′-O-Benzylidene Acetal Side Chain Structure as Potent α-Glucosidase Inhibitors - Xiaosong He; Jiahao Yi; Jianchen Yang; Genzoh Tanabe; Osamu Muraoka; Weijia Xie (Molecules)
A group of sulfonium and selenonium salts bearing diverse benzylidene acetal substituents on their side chain moiety were designed and synthesized. Compared with our previous study, structural modifications in this study focused on multi-substitution of the phenyl ring and bioisosteric replacements at the sulfonium cation center. In vitro biological evaluation showed that selenonium replacement could significantly improve their α-glucosidase inhibitory activity. The most potent inhibitor 20c (10.0 mg/kg) reduced postprandial blood glucose by 48.6% (15 min), 52.8% (30 min), and 48.1% (60 min) in sucrose-loaded mice, outperforming acarbose (20.0 mg/kg). Docking studies of 20c with ntMGAM presented a new binding mode. In addition to conventional hydrogen bonding and electrostatic interaction, amino residue Ala-576 was first identified to contribute to binding affinity through π-alkyl and alkyl interactions with the chlorinated substituent and aromatic ring. The selected compounds exhibited a high degree of safety in cytotoxicity tests against normal cells. Kinetic characterization of α-glucosidase inhibition confirmed a fully competitive inhibitory mode of action for these sulfonium salts.